Applications and Therapeutic Actions of Complementary and Alternative Medicine for Women with Genital Infection - Liu, Chenfang (Hindawi Publishing Corporation, 2014)
Genital infection is a common worldwide disease among females with clinical features such as bilateral lower abdominal tenderness, abnormal vaginal or cervical discharge, fever, abnormal vaginal bleeding, dyspareunia, vaginal itching, and adnexal tenderness, which can significantly impair women's health and quality of life. Genital infection is commonly treated with antibiotics, leading to an imbalance in gut flora due to prolonged use of antibiotics. Therefore, it is necessary to discover safe and efficacious alternative treatment strategies for patients with genital infection. Complementary and alternative medicine (CAM) is becoming increasingly prevalent among women with genital infection. CAM has interested the western mainstream medical community because of its less invasive, safe, effective, economical, and convenient therapies. CAM focuses on the prevention and treatment of disease and has become an important force in treating chronic disease. During the last few decades, the popularity of CAM has gradually increased. To further understand the efficacy of CAM in treating genital infection, our paper will review the current progress of treating genital infection including vulvitis, vaginitis, cervicitis, and pelvic inflammatory disease (PID) with CAM therapies. Several CAM strategies including traditional Chinese medicine (TCM), acupuncture, Psychology interference, and physical therapy are introduced in this review.